2013
DOI: 10.1002/hipo.22117
|View full text |Cite
|
Sign up to set email alerts
|

Representational demands modulate involvement of perirhinal cortex in face processing

Abstract: The classic view holds that the medial temporal lobes (MTL) are dedicated to declarative memory functioning. Recent evidence, however, suggests that perirhinal cortex (PrC), a structure within the anterior MTL, may also play a role in perceptual discriminations when representations of complex conjunctions of features, or of gestalt-characteristics of objects must be generated. Interestingly, neuroimaging and electrophysiological recordings in nonhuman primates have also revealed a face patch in the anterior co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 79 publications
6
26
0
1
Order By: Relevance
“…Even though we did not manipulate repetition in a condition-specific manner, the present results are consistent with the idea that this deflection may reflect access to recognition units and activation of a memory trace for the particular face that has become familiar with repetition (Zimmermann and Eimer, 2013). Our localization estimates and the observation of the sensitivity of the inferior and anterior temporal cortices to face orientation and identity are supported by fMRI studies (Sugiura et al, 2001; Rotshtein et al, 2005; Kriegeskorte et al, 2007; Nasr and Tootell, 2012; O'Neil et al, 2013) and are further confirmed with single cell recordings in non-human primates (Freiwald and Tsao, 2010). Similarly, lesion studies report that anterior temporal lesions result in face recognition impairments (Glosser et al, 2003; Barton, 2008; Gainotti and Marra, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Even though we did not manipulate repetition in a condition-specific manner, the present results are consistent with the idea that this deflection may reflect access to recognition units and activation of a memory trace for the particular face that has become familiar with repetition (Zimmermann and Eimer, 2013). Our localization estimates and the observation of the sensitivity of the inferior and anterior temporal cortices to face orientation and identity are supported by fMRI studies (Sugiura et al, 2001; Rotshtein et al, 2005; Kriegeskorte et al, 2007; Nasr and Tootell, 2012; O'Neil et al, 2013) and are further confirmed with single cell recordings in non-human primates (Freiwald and Tsao, 2010). Similarly, lesion studies report that anterior temporal lesions result in face recognition impairments (Glosser et al, 2003; Barton, 2008; Gainotti and Marra, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Several imaging studies have suggested that the human homologue to the monkey anterior face patch is located in the anterior (rostral) collateral sulcus in an area consistent with the PrC (O'Neil, Hutchison, McLean, & Kohler, 2014; Nasr & Tootell, 2012; Rajimehr et al, 2009; Rossion, Hanseeuw, & Dricot, 2012; Tsao et al, 2008). In humans, PrC activations are enhanced for faces relative to other objects (Lee, Bussey, et al, 2005; Lee, Scahill, & Graham, 2008), and face-specific activity in the PrC closely mirrors other face selective areas of the ventral stream (O'Neil, Barkley,& Köhler, 2013). Furthermore, the electrocorticogram of a patient with subdural grid electrodes in the right vATLs revealed a strong face-specific response from an electrode in perirhinal cortex that was reflected in both event-related potentials and broadbannd power changes (Tanji, Iwasaki, Nakasato, & Suzuki, 2012).…”
Section: The Ventral Anterior Temporal Lobesmentioning
confidence: 88%
“…The perirhinal cortex, which codes feature conjunctions viewpoint-invariantly (91), is involved in complex visual discrimination (92,93) and has been proposed as an extension of the representational hierarchy in the ventral system (94)(95)(96)(97)(98). These characteristics, along with the anatomical location of the perirhinal cortex, render this structure ideally situated to link perception and semantic memory, as required for generation and maintenance of face representations for face individuation (26) and face discrimination across different viewpoints (30,31,99). Our finding of familiarity-related activation increases in the hippocampus mirrors findings suggesting the hippocampus's role in activating preexisting knowledge about faces (100).…”
Section: Discussionmentioning
confidence: 99%
“…Such extended regions include structures within the medial temporal lobe (MTL), including the hippocampus, perirhinal cortex and amygdala (11,(23)(24)(25)(26)(27), the latter two of which exhibit face-preferential responses (15,28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation